How to Close Your Home - Virginia Peart (EDIS)
Closing Your Home has been developed to help Florida residents make plans for protecting their homes when they are to be absent. There are things you can do to protect your home from moisture problems, deterioration of the exterior, or the intrusion of burglars and vandals. This document is FCS3154, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2003. First published: January 1990. Reviewed: January 2003.